Stability analysis and stabilization control of discrete-time impulsive switched time-delay systems with all unstable subsystems - Jiang, Na; Sun, Yuangong (Nonlinear Analysis: Modelling and Control, 2024)
n this paper, stability analysis and stabilization control of discrete-time impulsive switched time-delay systems with all unstable subsystems are discussed. By utilizing a switching time-varying Lyapunov–Krasovskii functional and the mode-dependent interval dwell-time switching rule, we derive some more general stability theorems for the considered time-delay system with all subsystems being unstable. Moreover, we design a time-varying state feedback controller to ensure the stabilization of the resulting closed-loop system. Eventually, the theoretical findings are demonstrated utilizing numerical examples.
Keywords: discrete-time switched delay system; switching time-varying Lyapunov–Krasovskii functional; impulse; stability; stabilization